2018
DOI: 10.1080/21645515.2018.1450709
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 4, multicentre, randomized, single-blind clinical trial to evaluate the immunogenicity of the live, attenuated, oral rotavirus vaccine (116E), ROTAVAC®, administered simultaneously with or without the buffering agent in healthy infants in India

Abstract: Background: The World Health Organization recommends that rotavirus vaccines should be included in all national immunization programs. Some currently licensed oral rotavirus vaccines contain a buffering agent (either as part of a ready-to-use liquid formulation or added during reconstitution) to reduce possible degradation of the vaccine virus in the infant gut, which poses several programmatic challenges (the large dose volume or the reconstitution requirement) during vaccine administration. Because ROTAVAC®,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
(38 reference statements)
0
15
0
2
Order By: Relevance
“…The Indian study of RotaTeq® showed 83% three-fold rise (seroconversion) in serum IgA antibodies, however the study did not include a placebo arm [19]. A recent study in India also showed seropositivity rates ranging from 38.3% (95%CI: 32.8, 43.9) to 42.1% (95%CI: 36.6, 47.9), with three different formulations of Rotavac [20].…”
Section: Discussionmentioning
confidence: 99%
“…The Indian study of RotaTeq® showed 83% three-fold rise (seroconversion) in serum IgA antibodies, however the study did not include a placebo arm [19]. A recent study in India also showed seropositivity rates ranging from 38.3% (95%CI: 32.8, 43.9) to 42.1% (95%CI: 36.6, 47.9), with three different formulations of Rotavac [20].…”
Section: Discussionmentioning
confidence: 99%
“…В связи с тем, что корреляционный показатель иммунной защиты до настоящего времени не установлен 18 [31,38], для живых ротавирусных вакцин изучали возможность использования других факторов иммунологического ответа (ASC-клеток, секретирующих антител и Т-клеток) [39,40]. Многие исследователи при оценке эффективности вакцины как альтернативу корреляционным показателям иммунной защиты рассматривают так называемые «лабораторные маркеры» эффективности иммунитета, например уменьшение количества ротавирусов, выделяемых с фекалиями, что является прямым отражением способности вакцины подавлять размножение вируса в кишечнике [41]. Увеличение концентрации эпидермального фактора роста (epidermal growth factor, EGF) в слюне может выступать в качестве лабораторного маркера эффективности иммунитета, так как РВИ связана с повышением экспрессии гена IFI27 в подчелюстных слюнных железах.…”
Section: корреляционные показатели иммунной защиты при определении эфunclassified
“…При проведении клинических исследований вакцин Rotavac ™ (Индия) и Rotаsiil ™ (Индия) в Индии и Африке повышение числа инвагинаций в группах иммунизированных детей по сравнению с числом инвагинаций в контрольных группах было незначительным [41,51,52]. Тем не менее польза от вакцинации против РВИ, благодаря профилактике развития тяжелой диареи и смертельного исхода в результате ротавирусного заболевания, намного превышает риск развития инвагинации кишечника 22 .…”
Section: безопасность и реактогенность живых ротавирусных вакцинunclassified
“…B. Benninghoff (GSK) and Esmée de Wolde (Merck) produced updates on the Rotarix and RotaTeq vaccines, respectively (64,66). Mithu Raychaudhuri (Bharat Biotech International) described the introduction of Rotavac in India in 2016 (67). Using CRISPR/Cas 9 methodology, Houping Wang (Centers for Disease Control and Prevention) described the production of Vero cells in which the WDR62 gene was knocked out and which permitted propagation of RVA vaccine strains to higher titers; the technology will require further exploration before it can be used for vaccine manufacturing (68).…”
mentioning
confidence: 99%